Wawasan Kebinekaan Global Pada Anak Usia Dini di Ternate - Radjiman Ismail (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to provide an understanding of global diversity insights for early childhood. The research method using phenomenology. Data collection techniques using observation. Data analysis technique using descriptive analysis. The research sample is Early Childhood Education students in the Ternate region. It is important to give an understanding of global diversity to early childhood so that in the future they can live side by side with other humans, either from their own cultural area or from other cultures. Global diversity is a necessity so it cannot be denied. Schools must be able to prepare children to be able to communicate and understand other people's cultures so they can live in harmony. The research process uses culture cards. This card contains pictures of traditional houses, traditional clothes, dances, which come from all over Indonesia. When the student receives the card, opens and mentions the origin of the image obtained. The results of the study show that children can understand other people's cultures through traditional houses, traditional clothing, and regional dances. Research concludes that learning through culture cards is effectively used to develop understanding of other cultures.